School Building Energy Assessment Using Lean Energy Management Strategies - Ahamad, Abdul Hadi; Abidin, Nur IzieAdiana; Zakaria, Rozana; Aminudin, Eeydzah; Khan, Jam Shahzaib; Sahamir, Shaza Rina; Azman, Shamila; Redzuan, Amir Alhamdi; Lau, Santi Edra Nisa; Mohd Yusoff, Mohamad Faiz (Frontiers in Built Environment, 2022)
In Malaysia, there are approximately 10,2200 government schools and these schools’ electricity bills are under the responsibility of the Ministry of Education Malaysian Government. The demand for energy use is expected to rise dramatically in the coming years due to many factors such as the increasing number of students enrolment and the demand for a comfortable indoor environment in response to global climate effects. Therefore, there are many ideas, concepts, and technologies that have been introduced towards energy conservation in buildings. This study aims to identify key implementation of energy conservation measures and audit energy consumption of five (5) secondary schools. Case studies derived from schools that participated in Energy Efficiency Challenge hosted by Energy Commission. It was found that the school’s usage of electricity exceeded their need. Based on the implementation of energy management conservation measures throughout 2016 to 2019, there were gradual reductions and downtrends in energy consumption graphs.